Association between hepatic lipase -514 C/T promoter polymorphism and myocardial infarction is modified by history of hypercholesterolemia and waist circumference - Baylin, Ana (2009)
Background and aims: To examine whether the association between the 514 C/T polymorphism of the hepatic lipase gene and myocardial infarction (MI) is modified by history of hypercholesterolemia and increased waist circumference. Hepatic Lipase (HL) is a major determinant of HDL cholesterol, an established independent predictor of coronary heart disease (CHD) [1]. However, the role of HL in atherosclerosis remains uncertain. Overexpression of HL in transgenic and knockout animal models has resulted in both antiatherogenic and pro-atherogenic effects [2]. Although low HL activity in humans has been identified as a risk factor for CHD [3] the net effect of HL on CHD is hard to establish given its role in lipoprotein metabolism as both a lipolytic enzyme and as a ligand that facilitates uptake of lipoproteins [4]. Four linked polymorphisms (250 G to A, 514 C to T, 710 T to C, 763 A to G) have been identified in the promoter region of the HL gene [5]. These four poly- morphisms are in complete linkage disequilibrium and together define a common HL allele designed as 514 T allele. The T allele at position 514 of the HL gene is consistently associated with lower HL activity, higher HDL cholesterol, particularly HDL2 cholesterol, higher remnant-like particles, and triglyceride content and size of HDL and LDL particles [6]. Nevertheless, evidence of the effect of the 514 T allele on CHD is inconsistent. Some studies have shown no association [7-14], while others have shown an increased risk of CHD for carriers of the 514 T allele [15-19]. Surprisingly, the 514 T allele has not been inversely associated with CHD.